Investor behavior and stock market returns during Covid-19 - Sormunen, Roosa (2022)
In recent years, the Covid-19 pandemic has had significant effects on stock markets worldwide as no sectors have been able to hide from it. This special time period has also highlighted the role of psychological phenomena that have been more visible now than before.